Three-Dimensional Modeling of the Volcano Bandai Using Shape Texture - Vyatkin, Sergey I (International Journal of Natural Sciences Research, 2015)
This paper reports a three-dimensional modeling of the volcano Bandai near The Aizuwakamatsu City. Aizuwakamatsu is located in the western part of Fukushima Prefecture, in the southeast part of Aizu basin. A volcano model is coded as multilevel height map. To visualize the terrain, tessellation is not required. During the recursive voxel subdivision on each level, voxels are projected onto the base surface (plane). The altitude corresponding to this address and a level of details are calculated, and use it to modify coefficients of the plane equation. As a result was obtained a terrain surface modulated with the values from the altitude map.